PENGEMBANGAN DESTINASI WISATA NAGARI ANDALEH MELALUI PEMBANGUNAN BRANDING DAN POSITIONING DI KECAMATAN BATIPUH KABUPATEN TANAH DATAR - Khairil Anwar; Eri Gas Ekaputra; Oktavianus Oktavianus; Elvira Luthan; Varhanno Khallifhatul Khanh; Vitrya Qurratu Ayuni Khanh; Aufa Fikhriah; Resca Caesar Resti; Savira Nurul Hayuni (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Nagari Andaleh is a village in Batipuh District, Tanah Datar Regency, West Sumatra Province. This Nagari is rich with potential natural resources and human resources. Currently, this Nagari has become one of the tourist destinations in Tanah Datar Regency. The problem faced by the Nagari is the problem of branding and positioning tourist destinations. The purpose of this activity is to empower human resources to utilize natural resources as tourist destinations and develop the competitiveness of destination products to markets outside Tanah Datar Regency, accelerating the diffusion of technology and management from universities to partners. In particular, the purpose of the activity is to explore and build branding and positioning of tourist destinations in the Nagari. The activity is carried out in 3 stages. The first stage of preparation begins with socialization, contacting the Nagari government and related parties to determine the schedule of activities, and compiling activity modules, and preparing for the implementation of activities. The stage of implementing activities in the aspect of destination with destination quality control methods, training methods on strengthening Nagari institutions, branding and positioning development workshops, training methods for destination creation, and consulting. The final stage is the implementation of monitoring and evaluation of activities. The results of the activities are creating branding and positioning of Nagari tourist destinations, improving quality and destinations that are following natural resources, developing destination design innovations, and improving quality so that they can target the destination market. Mentoring activities need to be continued to help Nagari build tourist destinations Nagari Andaleh continues to grow.